The Seattle Criteria increase the specificity of preparticipation ECG screening among elite athletes. Issue 15 (27th June 2013) - Brosnan, Maria; La Gerche, Andre; Kalman, Jon; Lo, Wilson; Fallon, Kieran; MacIsaac, Andrew; Prior, David
Abstract : Background: In 2010, the European Society of Cardiology (ESC) released recommendations for the interpretation of the 12-lead ECG in athletes, dividing changes into group 1 (training related) and group 2 (training unrelated). Recently, the 'Seattle Criteria', a series of revisions to these recommendations, was published, with the aim of improving the specificity of ECG screening in athletes. Objectives: First, to assess the prevalence of ECG abnormalities in a cohort of elite Australian athletes using the 2010 ESC recommendations and determine how often group 2 ECG changes correlate with the evidence of significant cardiac pathology on further investigation. Second, to assess the impact of the 'Seattle Criteria' in reducing the number of athletes with ECG abnormalities in whom further cardiac testing is unremarkable ('false positives'). Design: 1197 elite athletes underwent cardiovascular screening between 2011 and 2012, of whom 1078 aged 16–35 years volunteered and were eligible to participate. Results: 186 (17.3%) had an abnormal ECG according to ESC recommendations and a further 30 (2.8)% had unclassified changes. Three athletes (0.3%) were found to have a cardiac abnormality on further investigation. Using the Seattle Criteria, the number of athletes classified as abnormal fell to 48 (4.5%, p<0.0001) and the three with an underlying cardiac abnormality were still identified. The improved specificity was due to reclassification of 71 athletes (6.6%) with an equivocal QTc interval, 42 (3.9%) with T wave inversion isolated to V1–2 and 22 (2%) with either isolated right axis deviation or right ventricular hypertrophy on voltage criteria. Conclusions: The 'Seattle Criteria' reduced the false-positive rate of ECG screening from 17% to 4.2%, while still identifying the 0.3% of athletes with a cardiac abnormality.